Associations of preterm birth and neonatal stress exposure with chronic pain in adulthood: results from the Gutenberg prematurity study - Tesarz, Jonas; Schuster, Alexander K.; Hermes, Michelle; Mildenberger, Eva; Urschitz, Michael Siegfried; Treede, Rolf-Detlef; Tost, Heike; Ernst, Mareike; Beutel, Manfred; Stoffelns, B.; Zepp, Fred; Pfeiffer, Norbert; et al. (Journal of psychosomatic research, 2024)
Although the effect of early childhood stress on central nervous pain processing is well known, studies on the association of prematurity and chronic pain are scarce. This study used data from a single-centre retrospective cohort study followed by a prospective clinical examination and pain assessment. The study was based on data from the local birth registry. Newborns born between 1969 and 2002 who had reached adulthood were eligible .. Using a selection algorithm, a study cohort stratified by gestational age (GA) was recruited. Chronic pain conditions were assessed using questionnaire and standardized pain drawings. Data on the pre-, peri- and postnatal clinical course was assessed from medical records. Multivariable logistic regression analyses were conducted to investigate associations between prematurity and chronic pain with adjustment for age, gender, socioeconomic status, and perinatal stress factors. 427 participants born preterm and full-term were included (age 28.5 ± 8.7 years). Chronic pain conditions were similarly common between groups with different levels of prematurity (GA ≥ 37 weeks: 34.5 %, GA33-36 weeks: 37.6 %, GA32-29 weeks: 25.2 %, GA < 29 weeks: 30.4 %, p = 0.20). In multivariable analyses, no association between low GA and the presence of chronic pain was found (OR = 0.99 (CI95 %: 0.94-1.04, p = 0.63); this was also true for a subanalysis of widespread pain. While neither fetal nutritional status nor perinatal stressors were associated with pain, exposure to maternal but not paternal smoking during pregnancy was associated with increased risk to develop pain (OR = 2.77 (CI95 %: 1.31-5.88, p = 0.008) in adults born preterm and full-term. This study suggests that prematurity by itself does not increase the risk of chronic pain later in life, but provides preliminary evidence for maternal smoking during pregnancy as risk factor.
Online verfügbar: 24. September 2024, Artikelversion: 27. September 2024
Gesehen am 11.03.2025